2007
DOI: 10.1210/en.2007-0127
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Increased Prolactin Gene Expression Requires Actin Treadmilling: Potential Role for P21 Activated Kinase

Abstract: Insulin-increased prolactin gene transcription in GH4 cells was enhanced by binding on fibronectin. This was mediated by receptor-like protein tyrosine phosphatase alpha, which activated Src, Rho, and phosphatidylinositol 3-kinase. It suggested that insulin signaling to gene transcription was partly dependent on actin rearrangement. This was confirmed through studies using inhibitors of actin treadmilling. Cytochalasin D, jasplakinolide, latrunculin B, and swinholide A altered the actin cytoskeleton of GH4 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Interestingly, PAK1 has been shown to function downstream of insulin in multiple cell types (36,37), one of which being L6 myotubes (21). Consistent with our data showing normal AKT activation in insulin-stimulated PAK1 KO skeletal muscle extracts, Klip and colleagues showed PAK1 (termed PAK65) to be downstream of PI-3 kinase in the insulin signaling cascade (21).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, PAK1 has been shown to function downstream of insulin in multiple cell types (36,37), one of which being L6 myotubes (21). Consistent with our data showing normal AKT activation in insulin-stimulated PAK1 KO skeletal muscle extracts, Klip and colleagues showed PAK1 (termed PAK65) to be downstream of PI-3 kinase in the insulin signaling cascade (21).…”
Section: Discussionsupporting
confidence: 89%
“…It has been previously reported that translocation of the translation machinery to dendritic spines is dependent on actin cytoskeletal dynamics and represent a key event in activity-dependent synaptic plasticity (31, 59). In addition, PAK has been previously implicated in insulin-mediated gene expression through the regulation of the actin cytoskeleton (60). In this study (60), actin depolymerizing agents did not affect nuclear mTOR activation induced by insulin, but reduced its activation in the cytoplasm, which indicates the specificity of these drugs to target specific populations of actin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PAK has been previously implicated in insulin-mediated gene expression through the regulation of the actin cytoskeleton (60). In this study (60), actin depolymerizing agents did not affect nuclear mTOR activation induced by insulin, but reduced its activation in the cytoplasm, which indicates the specificity of these drugs to target specific populations of actin filaments. In this regard, low concentrations of Lat A have been reported to specifically target actin filaments in dendritic shafts (where protein translation is generally thought to take place) but not in dendritic spines (31).…”
Section: Discussionmentioning
confidence: 99%
“…Swinholide A ( 1 ) displays impressive biological properties including antifungal activity and potent cytotoxicity against a number of tumor cells. Its mechanism of action has been clarified in detail and its activity has been attributed to its ability to dimerize actin and disrupt the actin cytoskeleton [79]. Today, swinholide A is one of the better-characterized membrane permeable and specific inhibitors of actin filament networks and is actively used in cell biology studies [10].…”
Section: Introductionmentioning
confidence: 99%